Putting People First: A Primary Health Care Success in Rural India - Vlassoff, Carol (Medknow Publications, 2010)
BACKGROUND: The World Health Report, 2008, contains a global review of primary health care on the 30th anniversary of the Declaration of Alma-Ata. The period covered by the study reported on here corresponds with that of the Report, allowing for a comparison of achievements and challenges in one primary health care centre vis-a-vis the WHO standards. MATERIALS AND METHODS: This study uses qualitative and quantitative data from a rural primary care facility in Western Maharashtra, collected over three decades. It analyzes the four groups of reforms defined by WHO in the context of the achievements and challenges of the study facility. RESULTS: According to the WHO Report, health systems in developing countries have not responded adequately to people’s needs. However, our in-depth observations revealed substantial progress in several areas, including in family planning, safe deliveries, immunization and health promotion. Satisfaction with services in the study area was high. CONCLUSION: Adequate primary health care is possible, even when all recommended WHO reforms are not fully in place.